Determination of Antioxidant Activity of some Varieties of Onion (Allium cepa L.) grown in Sudan - Sirag, Nizar; M Tajeldin, Imd; Abubakr, Mohamed; Mudathir, Alaa; Bashir, Isra Bashir; Mohammed, Salma (Gezira Journal of Health Sciences, 2018)
Background : Medicinal plants contain physiologically active ingredients that over the years have been exploited in traditional medicine for the treatment of various ailments.  Objectives: This study was undertaken to investigate the antioxidant activity of seven varieties of onion ( Allium cepa ) grown in Sudan.  Methods : The antioxidant capacity was conducted based on the ability of the plant extracts to scavenge DPPH radical. Results : The extracts exhibited a notable dose dependent inhibition of DPPH radical. Shendi (Red onion local strain) exhibited the highest antioxidant activity with EC50 25.25 µg/ml followed by Kassala (Red onion local strain) and white onion with less scavenging activity was produced by Green onion. Conclusion:   It can be concluded that Allium cepa could be a potential source of antioxidant principles.